ON URBAN ENVIRONMENT: A STUDY FOCUSING URBAN GEOMORPHOLOGY - Moura, Nina Simone Vilaverde (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
This work consists of an urban environment study in a sub-basin of Dilúvio stream's hydrographic basin located in Porto Alegre City Metropolitan Region, state of Rio Grande do Sul, Brazil, for apprehending the effects on and responses of the environment to the urbanization process in such area. Accordingly, a comprehensive knowledge of nature and society dynamics and how they articulate is envisaged. The environmental analysis is divided into the following stages: geomorphologic and superficial covering material characterization (original and anthropogenic morphology); analysis on the socioeconomic features from the study on the vegetal covering and soil use evolution and effects of the juridical aspects on the urban space arrangement. As a result of the research carried out, environmental data expressing the changes on the environment caused by urbanization processes were generated.